Design for small business recovery and optimization - Açaí too good (Research, Society and Development, 2024)
Brazil is the main producer and consumer of Açaí in the world. Açaí pulp has high nutritional value, in addition to preventing chronic degenerative diseases. Research carried out in Brazil by SEBRAE shows that around 31% of companies close their doors in the first year of operation, reaching 60% by the fifth year, as there are several related issues for an enterprise to perform well, grow and remain in business. Marketplace. And with the aim of assisting micro-enterprises in the city of Volta Redonda - RJ, a study was carried out at the company “Açaí bom loja VR LTDA”, located in the city of Volta Redonda. Consultancy was carried out in the following areas: management, finance, Marketing and qualities. The research methodologies applied were qualitative-quantitative and case study. A study was carried out on how the company operated before the intervention of students from the 10th period of Production Engineering and as a result of the evaluation, interventions were suggested with the aim of observing improvements in various sectors of the axes and even technological modernizations, such as: the implementation of financial software, field study regarding the quality of Açaí flavors over time. As a result, it was also observed that some Açaí flavors (Strawberry, Rafaello and Banana) lost their flavor over time, even though they were within the supplier's expiration date. presented these problems. Quality tools such as KPIs, PDCA and Ishikawa diagram were applied, which enabled the identification of problems and their possible solutions.